Dalla penna allo scalpello: analisi di archetipi per la morfologia delle lettere sull’epigrafe dei cibori di Cattaro - Zornija, Meri (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
The paper deals with the reconstructed inscription found on the well-known “lion’s” arcade and the fragments of pre-Romanesque ciboria found inside or near the cathedral of St. Tryphon in Kotor, Montenegro. The inscription, because of its unusual morphology, has so far provoked diverse interpretations regarding the dating of the reliefs. New arguments confirm the assumption that the inscription is inspired by the calligraphy of the Beneventan script. In this sense, first it is compared with epigraphic monuments of the early and mature Romanesque in Dalmatia and Apulia. Analogies are then made in the Beneventan codices, on the basis of which it is concluded that related graphic manner, distinguished by the decoration of letters with dots and circles, was used both in Apulia and Montecassino, but also in the Dalmatian scriptoria. The closest parallels are of local origin and related to the Benedictine sites and the literary production of the supposed scriptorium in Kotor, where the Beneventan codices served as inspiration for inscriptions made in stone.